Association between MDM2 rs 2279744 polymorphism and breast cancer susceptibility: a meta-analysis based on 9,788 cases and 11,195 controls - Gao J; Kang AJ; Lin S; Dai ZJ; Zhang SQ; Liu D; Zhao Y; Yang PT; Wang M; Wang XJ (Dove Medical Press, 2014)
Jie Gao,1,2,* An-Jing Kang,3,* Shuai Lin,1,* Zhi-Jun Dai,1 Shu-Qun Zhang,1 Di Liu,1 Yang Zhao,1 Peng-Tao Yang,1 Meng Wang,1 Xi-Jing Wang11Department of Oncology, 2Department of Nephrology, 3Department of Pathology, The Second Affiliated Hospital of Xi'an Jiaotong University, Xi'an, People's Republic of China *These authors contributed equally to this workPurpose: Previous studies have suggested associations between MDM2 (mouse double minute 2 homolog) polymorphisms and cancer risk. The aim of this study was to evaluate the relationship between the MDM2 rs 2279744 polymorphism and the susceptibility of breast cancer.Methods: We searched PubMed, Web of Knowledge, Embase, and the Chinese National Knowledge Infrastructure (CNKI) database for case–control studies published up to October 2013 that investigated MDM2 rs 2279744 polymorphism and breast cancer risk. Odds ratios (ORs) and 95% confidence intervals (CIs) were used to assess the strength of these associations.Results: A total of 19 studies were identified for the meta-analysis, including 9,788 cases and 11,195 controls. The variant heterozygote (TG) was associated with breast cancer risk in the overall population (TG vs TT: OR =1.10, 95% CI =1.04–1.17, P=0.001, P=0.23 for heterogeneity test). In the subgroup analyses by ethnicity, a significantly increased risk was observed among Asians (G vs T: OR =1.12, 95% CI =1.02–1.23, P=0.02, Phet=0.04; GG vs TT: OR =1.29, 95% CI =1.06–1.56, P=0.01, Phet=0.04; TG vs TT: OR =1.36, 95% CI =1.15–1.60, P=0.0004, Phet=0.45; dominant model TG+GG vs TT: OR =1.21, 95% CI =1.03–1.41, P=0.02, Phet=0.07). However, among Caucasians, rs 2279744 was associated with breast cancer risk in only one genotype (TG vs TT: OR =1.09, 95% CI =1.00–1.18, P=0.04, Phet=0.37). No publication bias was found in the present study.Conclusion: This meta-analysis provides evidence for the association between the MDM2 rs 2279744 polymorphism and breast cancer susceptibility. The results suggest that the MDM2 rs 2279744 polymorphism plays an important role in breast cancer, especially in Asians.Keywords: breast cancer, MDM2, single nucleotide polymorphism, susceptibility, meta-analysis